Leveraging on Digital Signage Networks to Bring Connectivity IOT Devices - David de Hoz, J. (2016)
The number of devices connected to the Internet currently exceeds the world's population by more than three times and this figure is expected to double in the next five years. The Internet of Things is a concept that describes this trend and outlines certain aspects of design and functionality that new devices must incorporate in order to successfully integrate with the Internet. In this sense, digital signage networks traditionally used for audiovisual media meet many of the characteristics required in the context of the Internet of Things: interoperability, mobility, scalability and ubiquity; relating both to the access and control of devices and to the information they generate. In this work, the power of using the proposed digital signage network as a substrate to be able to connect other types of devices so that they can take advantage of these networks is considered. To that end, the main existing problems in this integration are discussed, paying special attention to the bidirectional tunnel scheme used in the proposed digital signage solution. The effects of this tunneling approach are analyzed in scenarios with limited bandwidth and different solutions are proposed. This improves the performance of the tunnel in mobility, facilitating the integration of more devices into the Internet of Things by allowing them to be integrated into this type of network.